Pharmacodynamic and pharmacokinetic markers for anti-angiogenic cancer therapy: Implications for dosing and selection of patients. - Morotti, M; Dass, P; Harris, AL; Lord, SR (Springer, 2017)
Angiogenesis is integral to tumour growth and invasion, and is a key target for cancer therapeutics. However, for many of the licensed indications, only a modest clinical benefit has been observed for both monoclonal antibody and small-molecule tyrosine kinase inhibitor anti-angiogenic therapy. Pre-clinical and clinical studies have attempted to evaluate circulating, imaging, genomic, pharmacokinetic, and pharmacodynamic markers that may aid both the selection of patients for treatment and define dosing. Correct dosing is likely to be critical in the context of vascular normalization to allow better delivery of concomitant anti-cancer therapy and novel imaging techniques hold much promise in the early evaluation of pharmacodynamic response to improve efficacy.